PROSES BERCABANG DAN APLIKASINYA DALAM PENENTUAN PELUANG BERTAHAN SUATU MARGA - Andri Suryana (Faktor Exacta, 2011)
This research introduces branching processes as a stochastic process for estimating the number of the population of individuals at any generation “n”. One of the most interesting applications of branching processes is calculating the probability of eventual extinction. In probability theory, a branching process is a Markov chain that models a population in which each individual in generation “n” produces some random number of individuals in generation n + 1, according to a fixed probability distribution that does not vary from individual to individual. Branching processes are used to model reproduction. A central question in the theory of branching processes is the probability of ultimate extinction, where no individuals exist after some finite number of generations. Keywords: branching process, stochastic process, discrete time markov chain